Flora of Forest Reserves and Riparian Areas in Benin - Eben-Ezer Apelete; Jean Ganglo (Biodiversity Data Journal)
Benin government is committed to the overall strategy for the sacred forests and protected areas conservation through their integration into the national system of protected areas. This is due to the value of biodiversity and the considerable ethno-cultural and religious importance of the forests and protected areas. The project entitled “Project for the Integration of Sacred Forests into the System of Protected Areas of Benin (PIFSAP)” was initiated to preserve the biodiversity of the country by protecting and sustainably managing forest resources, biological and cultural heritage of local populations. Thus, all the sacred forests of Benin have been inventoried.The dataset published on GBIF website contains 8,488 occurrences of species collected in the forests and protected areas of Benin. After cleaning, the dataset was made accessible to the whole world via GBIF website: https://www.gbif.org/dataset/0740c09f-5cf6-48f0-8e94-abaa46f4b87b. This dataset is one of the largest databases published on “Centre d’Etudes et de Recherche sur les Forêts (CERF)” account and can be used for any purpose. The data collected are unique and provides information on species diversity found in the forest reserves of Benin.